Minutes of 18th technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 18th Technical and Progress Monitoring (TPM) meeting (session Il) of BRACU new campus, held on 15th July, 2019.